Systematic Literature Review: Could Plasma Convalescent Prevent Death on COVID-19? - Widjaja, Jordan Steven; Utami, Prawesty Diah; Putri, Jeanaya Hedya Alfara; Kusbijantoro, Yemima Billyana (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2021)
Abstract Introduction: The COVID-19 pandemic is still a global health problem, and the lack of effective and efficient treatment standards is one of the causes of the high morbidity and mortality rates. One approach that is often used in various cases of COVID-19 is convalescent plasma therapy. The administration of convalescent plasma is one of the treatment options that are often used in cases of COVID-19 with mild, moderate, severe, chronic, and critical symptoms. Objectives: The article review’s objective is to analyze of convalescent plasma transfusion in various cases of COVID-19 can prevent death and improve clinical outcomes. Methods: The PRISMA flowchart is applied to filter the literature that meets the inclusion criteria: published articles with experimental or observational research discussing the use of convalescent plasma in COVID-19 patients; published January 2020 - March 2021. We conducted article searches through PubMed, Google Scholar, and Science Direct. Assessment of the quality of the articles using the EPHPP form, and we chose ten articles. Result: The results of the qualitative analysis prove that convalescent plasma administration in various COVID-19 cases significantly reduces viral load, clinical improvement and prevents death in mild, moderate, and severe COVID-19s, but for terminal or critical cases, it does not show significant results. Discussion: The success rate of convalescent plasma therapy is determined by the high antibody titer in plasma donors, the distance between its administration and the onset of symptoms, and the patient's baseline condition before plasma administration. Based on these results, further research is needed to determine the standard dose and method of administration of convalescent plasma referring to the varied baseline conditions of patients. Abstrak Pendahuluan : Pandemik COVID-19 masih menjadi masalah kesehatan global, dan belum ditemukannya standar pengobatan yang efektif dan efisien menjadi salah satu penyebab tingginya angka morbiditas serta mortalitasnya. Salah satu pendekatan yang sering digunakan pada berbagai kasus COVID-19 adalah terapi plasma konvalesen. Pemberian plasma konvalesen  menjadi salah satu pilihan terapi yang sering digunakan pada kasus COVID-19 dengan gejala ringan, sedang, berat, kronis serta fase kritis. Tujuan : Tujuan penulisan artikel ini untuk menganalisis hasil penelitian lain yang mengulas tentang pemberian plasma konvalesen di berbagai kasus COVID-19. Metode : Metode penyusunan sistematik literatur review ini menggunakan diagram alir PRISMA untuk menyaring literatur yang memenuhi kriteria inklusi: artikel publikasi berupa penelitian eksperimental atau observasional yang membahas penggunaan plasma konvalesen pada pasien COVID-19; terbit bulan Januari 2020 – Maret 2021. Pencarian artikel dilakukan melalui tiga sumber: Pub Med, Google Scholar dan Science Direct. Penilaian kualitas artikel menggunakan formulir EPHPP, sehingga terdapat 10 artikel yang terpilih. Hasil : Hasil analisis kualitatif membuktikan bahwa pemberian plasma konvalesen pada berbagai kasus COVID-19 secara signifikan menurunkan viral load, perbaikan klinis, serta mencegah kematian pada pasien COVID-19 yang ringan, sedang dan berat, namun untuk kasus terminal atau kristis tidak menunjukkan hasil yang signifikan. Diskusi : Tingkat keberhasilan terapi plasma konvalesen ditentukan oleh tingginya titer antibodi dalam donor plasma, jarak pemberiannya dengan awal gejala serta kondisi awal pasien sebelum pemberian plasma. Berdasarkan hasil tersebut diperlukan penelitian lebih lanjut mengenai dosis dan cara pemberian plasma konvalesen mengacu pada kondisi awal pasien yang bervariasi.